Qualitative process evaluation of a new short-hospital-stay model with a general medicine focus in Germany (STATAMED): Study protocol - Katharina van Baal; Juliane Poeck; Clarissa Maria Lemmen; Wiebke Böhne; Johannes Jahn; Eva-Maria Wild; Nils Schneider (PLoS ONE, 2025)
Background The increasing number of elderly and multimorbid patients in need of care, coupled with a shortage of skilled health care professionals, poses significant challenges, especially in structurally underserved regions. STATAMED (funded by the G-BA Innovation Fund, 01NVF22103) represents a novel cross-sector care model emphasising short hospital stays with a general medicine focus for patients with (sub-)acute treatment needs. The intervention provides targeted, short-term inpatient care within STATAMED units, followed by rapid discharge and subsequent follow-up care in familiar environments. Key objectives include reduced emergency department visits, hospital stays and re-admissions, as well as the provision of needs-oriented health care. The broader evaluation comprises multiple quantitative and qualitative sub-studies. The present sub-study involves a qualitative process evaluation investigating the factors influencing acceptance, the degree of implementation and the impact on daily workflows and care structures at STATAMED sites. Methods The sub-study will employ a combination of qualitative health services research methods (i.e., focus group discussions, individual interviews, participatory observations, discussion and information forums) to capture the perspectives and experiences of three main stakeholder groups: (1) patients and their relatives, (2) health care providers and (3) the general population. Data collected through protocols and transcripts will undergo qualitative content analysis to identify recurring themes and insights. Discussion This sub-study seeks to elucidate the expectations, attitudes and needs of stakeholders, while assessing overall acceptance of the STATAMED model. Additionally, it aims to identify both facilitators and barriers to implementation, as well as the implications for work processes, collaboration and communication within daily care. The findings will inform strategies to optimise implementation, ensuring a successful transition to routine care. Given the political and public sensitivity surrounding health care system redesigns, particularly in rural areas, diverse stakeholder perspectives are incorporated. Trial registration The study was registered with the German Clinical Trials Register (Deutsches Register Klinischer Studien; DRKS00033801; date of registration: 22 March 2024).